Conceptualising patterns of career commitment: the leaving process in hospitality. Issue 1 (16th October 2019) - Gebbels, Maria; Pantelidis, Ioannis S.; Goss-Turner, Steven
Abstract : Purpose: This paper aims to examine the interplay between self-efficacy and career inheritance and its influence on career commitment in the hospitality sector. High labour turnover, unclear career paths and the transient nature of the work available in hospitality render it a suitable industry context that allows us to explore career commitment patterns. Design/methodology/approach: Drawing on life history methodology, semi-structured interviews were conducted with hospitality professionals holding a relevant degree but no longer employed in the hospitality industry. Findings: The findings revealed the interplay between self-efficacy, career inheritance and career commitment, as well as the speed of decline of career commitment, visualised as patterns of the leaving process. Although an infinite number of variations are possible, data unveiled the three main patterns. Research limitations/implications: The schematic illustrations of the patterns of the leaving process are not representative. The purposive sample comprises only ex-hospitality professionals, and generalisations can be considered in future studies. Practical implications: This newly conceptualised understanding of career commitment enables researchers to reconsider the fundamental reasons why individuals leave the hospitality industry, whilst also offering hospitality managers deeper insights into how the three identified patterns could inform recruitment and selection. Originality/value: This paper contributes to the literature through its meaningful theoretical extension in the context of career development studies. The unique concept of the leaving process addresses the prevalent issue of turnover and generates important implications.